The study of application of un-synchronized video cameras for 3-d motion analysis - Wan, X.; Xie, W. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The aim of this paper is to study the error induced by the time difference of the unsynchronized (no genlock connection) video cameras while they are applied to capture video for three-dimensional motion analysis, such as in competition arena. Three synchronized video cameras were used to capture data for this study at the rate of 200fields/second in laboratory and competition field of discus events. The motion of free fall is used to analyze the error of vertical position and velocity of the object. Finally the data of discus throw is discussed at different time-delay of the cameras.